Transformation Of Higher Education Marketing Strategy In The Digital Era: Implementation Model at Syekh Abdul Halim Hasan Institute, Binjai City - Akbar Sanjani, Maulana; Wijaya, Candra; Nur Nasution, Wahyudin (Edukasi Islami: Jurnal Pendidikan Islam, 2023)
This study examines the marketing strategies implemented by the Institute Sheikh Abdul Halim Hasan Binjai to improve power competition in the high education sector. This research aims at the application of mixed 4P marketing. Specifically, this study describes 1) the products produced by the Institute Sheikh Abdul Halim Hasan Binjai in improving power competitiveness of higher education, 2) prices offered by the Institute Sheikh Abdul Halim Hasan Binjai in improving power competitiveness of higher education, 3) places provided by the Institute Sheikh Abdul Halim Hasan Binjai in improving power higher education competitiveness, and 4) promotion strategies developed by the Institute Sheikh Abdul Halim Hasan Binjai in improving power higher education competitiveness. With an analysis of how universities develop their academic programs, establish tuition fees, optimize location strategically, and use promotional strategies, this study attempts to uncover the effectiveness of strategy in attracting candidate students and improving power competition. This study uses a qualitative approach, with data collected through structured interviews, observation, and analysis. Documents. Respondents covering stakeholders’ interests include the chairman of the foundation, leadership college high, lecturers, staff education, and students. Data collection and sampling methods snowball used to obtain comprehensive data. Data analysis was carried out using the interactive model of Miles and Huberman, namely data condensation, data presentation, and retrieval conclusion. Triangulation technique applied to validate data and ensure reliability. Findings from the study show that aligning academic programs with market demand, maintaining competitive and affordable tuition fees, choosing strategic campus locations, and integrating traditional and digital promotional strategies significantly contribute to improving the power competitiveness/superiority of the competitive Institute Sheikh Abdul Halim Hasan Binjai. Next, in the adaptation curriculum, collaboration and improvement facilities are very important in maintaining relevance and pulling candidate students. Based on the findings, the Institute Sheikh Abdul Halim Hasan Binjai recommended continuing to increase the curriculum and align it with market and industrial world needs that continue to grow and develop. In addition, it is necessary to further integrate digital marketing strategies to expand reach and maintain power in the increasingly competitive education sector.